Character of advance and retreat of the southwest sector of the British-Irish Ice Sheet during the last glaciation. (1st September 2022) - Giglio, Cristiana; Benetti, Sara; Plets, Ruth M.K.; Dunlop, Paul; Ó Cofaigh, Colm; Sacchetti, Fabio; Salomon, Elaine
Abstract: Relict landforms and sediments across former glaciated settings provide information about ice-sheet dynamics and can contribute to the understanding of the behaviour of contemporary ice masses, for which observations are limited in spatial and temporal extent. In this study, we focus on the shelf offshore southwest Ireland, in the Celtic Sea, which was once occupied by the Irish Sea Ice Stream (ISIS), the largest ice stream draining the southern portion of the marine-terminating British-Irish Ice Sheet (BIIS). Newly acquired high-resolution multibeam echosounder, sub-bottom and core data enabled the investigation of the shelf geomorphology and of the sedimentology and chronology of glacial and glacimarine sediments. A suite of drumlins records ice sheet flow from the coastline towards the central part of the shelf in southwest Ireland. Pre-existing highs in the seafloor topography promoted the formation of arcuate and transverse landforms interpreted as a grounding-zone wedge and moraines and they document episodic retreat of the ISIS across this portion of the shelf. Observed lithofacies show consolidated subglacial till and laminated fine muds. The sediments provide evidence of ice grounded ca. 30 km off the south-west Irish coastline with subsequent deglaciation occurring under glacimarine conditions. These new data refine the current reconstructions of the dynamics of the southern BIIS. They reveal for the first time the interplay of marine- and land-based ice and the presence of grounded ice offshore SW Ireland. This study highlights the importance of high-resolution data in revealing palaeo-landscapes as valuable analogues to test possible scenarios of modern ice sheet changes. Highlights: We present new marine high-resolution multibeam, sub-bottom and core data from Ireland. A suite of glacial and glacially-related landforms is mapped on the Celtic Sea shelf. Evidence shows that ice was grounded ∼30 km offshore of SW Ireland. Deglaciation occurred under glacimarine conditions. Dating refines the current reconstructions of the dynamics of the southern BIIS.